What drives live-stream usage intention? The perspectives of flow, entertainment, social interaction, and endorsement - Chen, Chia-Chen; Lin, Yi-Chen (Telematics and informatics, 2018)
•This study investigates the usage intention for live-stream service.•The usage intention is directly affected by positive attitude and perceived values.•The usage intention for differences between sex and gender are also investigated. Live-stream is the real-time audio and video transmission of an event over the Internet. Since a live-stream can also be interactive, it has some of the characteristics of a small community. People often become addicted to television, movies, or video blogs for the sake of entertainment. They can also become blind and obsessive about worshiping popular idols. Moreover, their willingness to use media is affected by their own perception of the media or their expectation of the benefits. This study therefore proposes four key factors: flow, entertainment, social interaction, and endorsement. We use path analysis to test their relationships with attitude, perceived value and watching intention to understand the influential factors and channels that induce audiences to watch live-streaming events. Analysis of 313 valid responses to a survey questionnaire indicate that approximately 65% of Taiwanese people watch live-streams via social network sites. In general, they watched live-streams simply because they liked to do so. The main reason behind their favorable impression of live-streaming was that live-streams made people happy and relieved stress. Secondly, people were attracted by the charm of the streamers, but the attraction differs slightly by gender. Females developed a more favorable impression of a live-stream when they admired the streamer. Males, on the other hand, developed a more favorable impression of a live-stream when they interacted with the streamer or other audience members. Young people tended to like live-streaming because it gave them a sense of flow, while older people were not affected by flow. This study contributes to the development of live-stream services and future studies on live-streaming.